2017
DOI: 10.1108/ijqrm-06-2016-0075
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic analysis of two non-identical unit parallel system incorporating waiting time

Abstract: Purpose The purpose of this paper is to evaluate various reliability metrics such as transition state probabilities, availability, reliability, mean time to failure and expected profit of two non-identical unit parallel system incorporating waiting time. Design/methodology/approach The present paper investigates the reliability of two non-identical unit parallel system with two types of failures: common cause failure and partial failure. Moreover, waiting time to repair, a significant aspect of reliability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Taking Laplace transformation on both sides of Eqs (18)(19)(20)(21)(22)(23) and solving for B * * 0 ðsÞ; we get…”
Section: Busy Period Of Servermentioning
confidence: 99%
See 1 more Smart Citation
“…Taking Laplace transformation on both sides of Eqs (18)(19)(20)(21)(22)(23) and solving for B * * 0 ðsÞ; we get…”
Section: Busy Period Of Servermentioning
confidence: 99%
“…Kumar et al [20][21][22] investigated the impact of various kind of priorities and preventive maintenance on systems of Weibull distributed random variables. Chopra and Ram [23] proposed a stochastic model for parallel system with waiting time. Dey et al [24] provided an extension of generalized exponential distribution having application in Ozone data.…”
Section: Introductionmentioning
confidence: 99%
“…Some instrumental approaches that provide detailed perception of the reliability of modern systems are stochastic modeling, use of the universal generating function, signature analysis, and survival signature methods. Stochastic modeling (Dhillon and Yang, 1992;El-Sherbeny, 2013;Chopra and Ram, 2017). employs probabilistic analysis for assessing the reliability of systems emphasizing randomness and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers concluded that the availability, reliability and the MTTF of parallel system shrinks with the increment in common cause failure rate and human error rate. Chopra and Ram (2017) further evaluated the reliability measures of the dissimilar units parallel system by incorporating waiting time. Agnihotri and Satsangi (1996) analyzed two distinct parallel units system with priority based repair, inspection and post repair.…”
Section: Introductionmentioning
confidence: 99%